Compositional effects on the mechanical and thermal properties of MoNbTaTi refractory complex concentrated alloys. (January 2022) - Startt, Jacob; Kustas, Andrew; Pegues, Jonathan; Yang, Pin; Dingreville, Rémi
Graphical abstract: Highlights: We investigated the mechanical and thermal properties of MoNbTaTi RCCAs. High Mo content yields high yield strength. High Mo content promotes a shift from metallic to covalent bonding. MoNbTaTi RCCAs show good high-temperature stability regardless of the composition. Abstract: Refractory complex concentrated alloys are an emerging class of materials that attracts attention due to their stability and performance at high temperatures. In this study, we investigate the variations in the mechanical and thermal properties across a broad compositional space for the refractory MoNbTaTi quaternary using high-throughput ab-initio calculations and experimental characterization. For all the properties surveyed, we note a good agreement between our modeling predictions and the experimentally measured values. We reveal the particular role of molybdenum (Mo) to achieve high strength when in high concentration. We trace the origin of this phenomenon to a shift from metallic to covalent bonding when the Mo content is increased. Additionally, a mechanistic, dislocation-based description of the yield strength further explains such high strength due to a combination of high bulk and shear moduli, accompanied by the relatively small size of the Mo atom compared to the other atoms in the alloy. Our analysis of the thermodynamics properties shows that regardless of the composition, this class of quaternary alloys shows good stability and low sensitivity to temperature. Taken together, these results pave the way for the design of new high-performance refractory alloys beyond the equimolar composition found in high-entropy alloys.